2012
DOI: 10.1097/inf.0b013e318233049d
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a 13-valent Pneumococcal Conjugate Vaccine in Healthy Infants and Toddlers Given With Routine Pediatric Vaccinations in Canada

Abstract: Responses to routine childhood vaccines did not differ with PCV7 or PCV13 coadministration. Serotype-specific pneumococcal antibody concentrations were protective. The safety profile of PCV13 was favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 21 publications
3
27
0
1
Order By: Relevance
“…In a recent post-licensure, indirect cohort study, an antibody concentration against serotype 19A of 1 mg/ml was shown to be adequate to prevent most of the IPD cases due to this serotype [37]. This antibody level was in the range of values produced by PCV13 after both the infant series and the booster dose, independent of the schedule used, as clearly shown by Rodgers et al, who analyzed several immunogenicity studies in which PCV13 was administered on the 2 + 1 schedule [14] and by several authors who have studied PCV13 on the 3 + 1 schedule [38][39][40]. Conversely, the very good results shown by some of the studies that have evaluated PCV10 are surprising and difficult to explain when the putative correlate of protection for serotype 19A and the amount of functioning cross-reactive antibodies produced by conjugate serotype 19F included in PCV10 are considered.…”
Section: Expert Commentarymentioning
confidence: 84%
“…In a recent post-licensure, indirect cohort study, an antibody concentration against serotype 19A of 1 mg/ml was shown to be adequate to prevent most of the IPD cases due to this serotype [37]. This antibody level was in the range of values produced by PCV13 after both the infant series and the booster dose, independent of the schedule used, as clearly shown by Rodgers et al, who analyzed several immunogenicity studies in which PCV13 was administered on the 2 + 1 schedule [14] and by several authors who have studied PCV13 on the 3 + 1 schedule [38][39][40]. Conversely, the very good results shown by some of the studies that have evaluated PCV10 are surprising and difficult to explain when the putative correlate of protection for serotype 19A and the amount of functioning cross-reactive antibodies produced by conjugate serotype 19F included in PCV10 are considered.…”
Section: Expert Commentarymentioning
confidence: 84%
“…[11] In addition, given the immunogenicity studies of PCV13 the immune responses for serotype 3 differ from that for the other serotypes: lower antibody titers and no or little booster effect (but no hyporesponsiveness). [18][19][20][21][22] 6 *χ 2 for trend P=0.031 Nevertheless, the response for serotype 3 on opsonophagocytic activity assay is high when the infant series and toddler dose of PCV13 is used. [19,20] There is a recent report on a three-year-old girl who developed a parapneumonic empyema caused by serotype 3, while she was fully vaccinated with PCV13, but in a 2 þ 1 schedule.…”
Section: Discussionmentioning
confidence: 94%
“…The limited effectiveness of PCV-7 was reported in Utah as a result of the rapid emergence of IPD, particularly empyema, due to non-PCV-7 serotypes (10,19,39,40). These findings encouraged the development of new pneumococcal conjugate vaccines with additional serotypes, namely, PCV-10 and PCV-13 (41,42). However, clinical trials showing the efficacy of PCV-10 and PCV-13 against consolidated pneumonia and IPD have been limited.…”
Section: Discussionmentioning
confidence: 98%